Video Analysis of Amir Nasution's Monologue Theater Performance by Teuku Rifnu Wikana Based on the Theory of Understanding and Characteristics of Drama - Witri Kharisma Azhari (Research in Education, Technology, and Multiculture, 2022)
Abstract: Drama is a play in which there is conflict and is played with a happy or sad ending, for the purpose of entertainment. The purpose of this study is to describe the theory of understanding and characteristics of drama in the performance of Teuku Rifnu Wikana's Nasution monologue. Qualitative analysis method is the method used in this study. It was found that the performance of the monologue Nasution by Teuku Rifnu Wikana was successful because it was in accordance with the meaning and characteristics of drama. The results shown in this study are that Nasution's performance is included in the type of monologue drama, because it is played by one actor. In the drama, Nasutin's monologue is complemented by stage decorations so as to liven up the atmosphere of the drama.   Keywords: drama, characteristics of drama, drama nasution